2020
DOI: 10.1371/journal.pone.0238459
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with smartphone addiction: A comparative study between Japanese and Thai high school students

Abstract: Background Smartphone addiction is a growing social problem with adverse health outcomes. There are few comparative studies in Asia that examine factors associated with smartphone addiction. The current study aimed to address this research gap by presenting a comparative analysis of factors associated with smartphone addiction in Japan and Thailand, two countries heterogeneous in both their level of economic development and culture. Methods Participant data were collected using two population-based surveys. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
3
15
1
3
Order By: Relevance
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…To date, although a few studies have examined internet use and smartphone use in adolescents, middle and high school students (17)(18)(19)(20)(21)(22), few studies examined the smartphone use pattern and PMPU among university students in China during the COVID-19 pandemic. Furthermore, no studies have examined the association between PMPU and life satisfaction using standard structured instruments.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that m‐learning is a natural evolution of e‐learning caused by the ubiquitous character of mobile devices (Barnes et al, 2019; Zhai & Shi, 2020). The users, who are familiar with, or even addicted (Andrade et al, 2020; Kuem et al, 2020; Tangmunkongvorakul et al, 2020) to mobile gadgets, do not have to change anymore the device when shifting from basic phone‐related activities (calls, messaging, and emails) to personal needs (order food, shopping, booking for various services), entertainment (social media, games, movies, news), but also working or learning (Fu et al, 2020). Moreover, studies like (Buchmann & Karagiannis, 2017) demonstrate that m‐learning is not exclusively designed for schools or universities.…”
Section: Introductionmentioning
confidence: 99%
“…As smartphones have become a necessity, some researchers have reported gender differences in smartphone addiction in different student populations, although these differences are inconsistent [ 29 , 32 , 33 ]. Increasing smartphone usage was noticed in a parent–children relationship study among elementary school students in Korea, where it was found that 80.4% of participants started smartphone use below 10 years old.…”
Section: Introductionmentioning
confidence: 99%